A Preseason Cardiorespiratory Profile of Dancers in Nine Professional Ballet and Modern Companies. Issue 2 (June 2014) - Bronner, Shaw; Ojofeitimi, Sheyi; Lora, Jennifer Bailey; Southwick, Heather; Kulak, Michelina Cassella; Gamboa, Jennifer; Rooney, Megan; Gilman, Greg; Gibbs, Richard
While studies have investigated the physical demands of dance in terms of cardiorespiratory fitness, there are no recent comparisons of cardiorespiratory response to exercise among professional dancers of different genres. Our purpose was to: 1. develop a cardiorespiratory profile of professional dancers; 2. investigate differences in peak and recovery heart rate (HR) between professional modern and ballet dancers using an accelerated 3-minute step test; 3. demonstrate the relationship between cardiorespiratory variables; and 4. investigate the effects of company and work variables on the dancers' cardiorespiratory profiles. We hypothesized greater cardiorespiratory fitness in modern dancers than in ballet dancers, due to the nature of their repertory. Furthermore, we hypothesized that company profiles would reflect differences in work variables. Two hundred and eleven dancers (mean age 24.6 ± 4.7) from nine companies (two modern and seven ballet) performed a 3-minute step test. Demographics, height, mass, blood pressure (BP), smoking history, and resting peak and recovery HR were recorded. Body mass index (BMI) and fitness category were calculated. Independent t-tests were used to compare differences in demographics and cardiorespiratory variables due to genre, MANOVA were conducted to compare differences due to company, and correlations were calculated to determine the relationships between cardiorespiratory variables (p < 0.05). Modern dancers demonstrated higher mass and BMI, lower BP, lower resting HR and HR recovery, and a higher percentage were categorized as "fit" compared to ballet dancers (p < 0.03). There were differences between companies in age, experience, BMI, BP, resting, peak, and recovery HR, and fitness category (p < 0.001). The differences in cardiorespiratory fitness levels that may be related to rigor of repertory, rehearsal and performance seasons, or off-season exercise training are discussed. Results support the need for comprehensive physical fitness screening to identify dancers who could benefit from aerobic conditioning to enhance overall performance preparedness and to minimize fatigue effects.